2015
DOI: 10.1007/s00161-015-0460-3
|View full text |Cite
|
Sign up to set email alerts
|

Modeling rammed earth wall using discrete element method

Abstract: Rammed earth is attracting renewed interest throughout the world thanks to its "green" characteristics in the context of sustainable development. Several research studies have thus recently been carried out to investigate this material. Some of them attempted to simulate the rammed earth's mechanical behavior by using analytical or numerical models. Most of these studies assumed that there was a perfect cohesion at the interface between earthen layers. This hypothesis proved to be acceptable for the case of ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 50 publications
1
22
0
1
Order By: Relevance
“…e wall was modeled with 12 layers of 11.4 cm each (named "intralayer") and thin layers of 1 cm (named "interlayer") between the earthen layers. Indeed, the role of the interlayers may not be predominant in the case of vertical loads but important in the cases where the interfaces are more solicited [17]. In the present study where the walls are subjected to horizontal loads, the e ects of interlayers on the model might have a signi cant impact on the results.…”
Section: Numericalmentioning
confidence: 73%
See 3 more Smart Citations
“…e wall was modeled with 12 layers of 11.4 cm each (named "intralayer") and thin layers of 1 cm (named "interlayer") between the earthen layers. Indeed, the role of the interlayers may not be predominant in the case of vertical loads but important in the cases where the interfaces are more solicited [17]. In the present study where the walls are subjected to horizontal loads, the e ects of interlayers on the model might have a signi cant impact on the results.…”
Section: Numericalmentioning
confidence: 73%
“…For the numerical modelling, due to the simplicity, the earthen layers are usually assumed homogeneous and the interfaces are added between layers [17]. However, the above experimental results showed that there was a difference in the cohesions and the friction angles between the upper and middle parts of an earthen layer.…”
Section: Numerical Modelling Of Re Shear Wallsmentioning
confidence: 99%
See 2 more Smart Citations
“…In last decade several studies were carried out to numerically model the behaviour of earthen materials under static [7,8,9,11,12,13,14,15,16,17] and under pseudo-dynamic loading [18,19,20]. This article presents a comparative study on the numerical modelling of three different earthen materials under static in-plane loading.…”
Section: Introductionmentioning
confidence: 99%